Évaluation d’une intervention de groupe d’approche féministe auprès de femmes victimes d’agression sexuelle - Bergeron, Manon; Hébert, Martine (Child abuse & neglect, 2006)
The present study evaluates a group intervention using a feminist approach for women experiencing sexual abuse in childhood or adulthood in order to measure changes associated with participation in a group intervention and verifies whether effects are maintained over time. The present study relates effects of the group intervention in terms of psychological distress, depression symptoms, post-traumatic stress symptoms and feelings of guilt and helplessness.The sample consists of 26 women participating in a group intervention offered by sexual assault centers in Quebec (CALACS - Centre d'aide et de lutte contre les agressions à caractère sexuel).Results show significant differences between pretest and post-test scores obtained one week following the end of the group intervention and gains are maintained at follow-up 3 months later. The findings suggest that participation in the group intervention is associated with a reduction of psychological distress, depression symptoms, post-traumatic stress symptoms and feelings of guilt and helplessness in adult women reporting sexual abuse.
Keywords: discipline; outils; recherche en milieux de pratique; ressource en ligne; sciences humaines; sexologie; thématiques; violences; violences contre les femmes*; violences sexuelles